(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Research can be expressed in a targeted theoretical way. In this case, the main emphasis in the preparation of the program is on theoretical and methodological problems: interesting the issues will focus on the study of scientific literature, the construction of the concept of the subject of research, etc. In this case, the object of research is determined when performing additional theoretical work. The study works on the program taking into account the social characteristics of the social object after receiving a specific social order. Sociologist his research the subject searches for the object of study in accordance with its concept.